Показники ефективності системи обслуговування адаптивної автоматизованої системи управління - Балтовський, Олексій (Видавництво Національного університету «Львівська політехніка», 2009)
Common requirements, basic positions of the technical providing, question of methodology and algorithms of détermination of efficiency of the system of informative maintenance of the integrated automated system of opérations management are considered in article
Keywords: informative system; fiinctions; criteria of estimation; efficiency; адаптивна автоматизована система управління; аналіз літературних джерел